Aspek sosial kognitif siswa dalam mengadaptasikan teknologi di era society 5.0 - Khoiriyah, Dhuhrotul; Thohir, Muhammad (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2023)
Students' social cognition refers to their ability to think and interact with the social environment. Albert Bandura's social cognitive theory states that individuals can learn and choose to perform or refrain from certain behaviors by observing others. This learning process is known as observational learning. Currently, observational learning is not only conducted in real-life settings but also in virtual environments. The presence of technology in social cognitive theory is understood as a medium for implementing modeling learning to students. The advent of technology in the Society 5.0 era is said to be capable of replacing the role of a teacher. So, how can students adapt to technology? The aim of this research is to understand the social cognitive aspects of students in adapting to technology in the Society 5.0 era. The method in this research employs a qualitative descriptive approach using a literature study method, which involves gathering data from various digital literary sources such as books, articles, and journals that support the research, with a time limitation of the last 3 years (2019-2022). This research provides new insights into the forms of technology adaptation in the Society 5.0 era, which include: 1) Students building awareness of the importance of technology, 2) the students are knowledgeable about the proper use of technology, 3) students utilizing technology for work flexibility and critical thinking. From the conceptual findings, this study offers new information about the reconstruction of adaptation forms that can be applied in every future era, particularly in the field of education.